2016
DOI: 10.1002/cmr.a.21412
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐state nuclear magnetic resonance and nuclear quadrupole resonance as complementary tools to study quadrupolar nuclei in solids

Abstract: Solid-state nuclear magnetic resonance (SSNMR) spectroscopy has largely overtaken nuclear quadrupole resonance (NQR) spectroscopy for the study of quadrupolar nuclei. In addition to information on the electric field gradient, SSNMR spectra may offer additional information concerning other NMR interactions such as magnetic shielding. With continued technological advances contributing to developments such as higher magnetic fields, SSNMR boasts several practical advantages over NQR. However, NQR is still a relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 74 publications
(89 reference statements)
0
21
0
Order By: Relevance
“…As ar esult, the quadrupolar coupling yields information on the electronic structure,which can be used to refine crystal structures [42] and learn more about chemical bonding.The reader is referred to an article detailing the interpretation of the quadrupolarcoupling tensor in terms of structure and bonding. [44] Rather than broad line shapes as seen in NMR (on the order of several to tens of MHz), however, pure NQR yields relatively sharp resonances (on the order of tens of kHz in this work;s ee Supporting Information), the frequencies of which relate to the quadrupolar interaction. Fortunately,n uclear quadrupole resonance (NQR) spectroscopy is well-suited to study nuclei subject to large quadrupole couplings,which is the case for quadrupolar halogens,and can be performed using the same radiofrequencye quipment included with aS SNMR spectrometer but in the absence of am agnetic field.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…As ar esult, the quadrupolar coupling yields information on the electronic structure,which can be used to refine crystal structures [42] and learn more about chemical bonding.The reader is referred to an article detailing the interpretation of the quadrupolarcoupling tensor in terms of structure and bonding. [44] Rather than broad line shapes as seen in NMR (on the order of several to tens of MHz), however, pure NQR yields relatively sharp resonances (on the order of tens of kHz in this work;s ee Supporting Information), the frequencies of which relate to the quadrupolar interaction. Fortunately,n uclear quadrupole resonance (NQR) spectroscopy is well-suited to study nuclei subject to large quadrupole couplings,which is the case for quadrupolar halogens,and can be performed using the same radiofrequencye quipment included with aS SNMR spectrometer but in the absence of am agnetic field.…”
Section: Introductionmentioning
confidence: 63%
“…Fortunately,n uclear quadrupole resonance (NQR) spectroscopy is well-suited to study nuclei subject to large quadrupole couplings,which is the case for quadrupolar halogens,and can be performed using the same radiofrequencye quipment included with aS SNMR spectrometer but in the absence of am agnetic field. [44] Rather than broad line shapes as seen in NMR (on the order of several to tens of MHz), however, pure NQR yields relatively sharp resonances (on the order of tens of kHz in this work;s ee Supporting Information), the frequencies of which relate to the quadrupolar interaction. While spin-3/2 nuclei have asingle transition (1/2!3/2), spin-5/2 nuclei exhibit two possible single-quantum transitions (1/2!3/2 &3 /2!5/2).…”
Section: Introductionmentioning
confidence: 99%
“…NQR is suited for spins with large quadrupolar interactions. 7 The authors also demonstrated, for the first time, the 35 Cl and 79 Br NMR of bulk and nanocrystalline CsPbX 3 collected with the special WURST-CPMG sequence. 8 In the main text and Supporting Information, the authors provided introductory tutorials of NMR and NQR for halide spins.…”
mentioning
confidence: 91%
“…Despite the availability of higher applied magnetic fields for NMR spectroscopy, the covalently bonded quadrupolar halogens, including 35/37 Cl (spin I =3/2), 79/81 Br (spin I =3/2), and 127 I (spin I =5/2), remain challenging or unamenable to SSNMR due to substantial quadrupolar spectral broadening. Fortunately, nuclear quadrupole resonance (NQR) spectroscopy is well‐suited to study nuclei subject to large quadrupole couplings, which is the case for quadrupolar halogens, and can be performed using the same radiofrequency equipment included with a SSNMR spectrometer but in the absence of a magnetic field . Rather than broad line shapes as seen in NMR (on the order of several to tens of MHz), however, pure NQR yields relatively sharp resonances (on the order of tens of kHz in this work; see Supporting Information), the frequencies of which relate to the quadrupolar interaction.…”
Section: Introductionmentioning
confidence: 99%